Fibroblasts from PS1 Mutated Pre-Symptomatic Subjects and Alzheimer's Disease Patients Share a Unique Protein Levels Profile - Magini, Alessandro; Urbanelli, Lorena; Ciccarone, Virginia; Tancini, Brunella; Polidoro, Mario; Timperio, Anna Maria; Zolla, Lello; Tedde, Andrea; Sorbi, Sandro; Emiliani, Carla (Journal of Alzheimer's disease, 2010)
In Alzheimer's disease (AD), a major goal is to improve early detection, as the diagnosis cannot be made until patients exhibit a noticeable decline in cognition and the brain is irreversibly damaged. With this aim in mind, we performed proteome analysis of familial AD fibroblasts from both demented and pre-symptomatic subjects, using a 2D-PAGE based approach and then identifying proteins by mass spectrometry. We compared primary fibroblast cultures from skin biopsy of presenilin 1 (PS1) mutated patients, pre-symptomatic subjects carrying mutations in the PS1 gene but healthy at the time of skin biopsy, and age-matched individuals as control. 15 differentially expressed proteins were identified in PS1 mutated fibroblasts, related to cell adhesion and cytoskeleton, energy and glucose metabolism, stress response and ubiquitin-proteasome system, and signal transduction. Interestingly, many of these proteins have been previously associated with AD and neurodegeneration. Overall results indicated that a unique protein profile can be identified by peripheral cell analysis of PS1 mutated individuals, and showed that fibroblasts are a useful cell model for pathological investigations as well as identification of potential biomarkers for AD diagnosis at early stages.